ICT COMPETENCIES OF PEDAGOGICAL WORKERS - HODIS, Vladislav (Trends in education, 2009)
The Paper aims at questions of pedagogical competencies in the field of Information and Communication Technologies. Presented is definition of competency of using digital camera, digital video camera and microphone in mentioned instruction.
Keywords: Pedagogical competencies; Information and Communication Technologies (ICT); ICT competencies of teacher.